2018
DOI: 10.1080/01904167.2018.1549673
|View full text |Cite
|
Sign up to set email alerts
|

Chelated zinc leaf application on nutrients concentration and yield of Mombasa grass

Abstract: The intensification of livestock yield requires advances in the management and fertilization of forage crops. This study was conducted to determine the dry weight yield (DWY) along with the concentration and amount of nutrients of Megathyrsus maximum cv. Mombasa. The treatments were arranged in a factorial scheme 6 Â 2, six leaf rates of Zn chelate and two soil types (Entisols and Ultisol) with low and medium Zn content and four replicates. Entisols with low Zn content and Ultisol with average Zn content were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The treatment foliar spray of 0.5 % TNAU Zn EDTA (T 10 ) recorded significantly higher Zn content and control (NPK alone -T 1 ) recorded lowest Zn content. This is in agreement with the findings of Teixeira et al, (2019) who reported that Zn content and Zn uptake in the Mombasa grass was directly proportional to the rate of foliar applied chelated Zn, contributing to the yield of better quality forage. The improvement in the Zn concentration and uptake observed in this experiment comparing ZnSO4 and Zn-EDTA, is similar to that reported by Gangloff et al, (2002).…”
Section: Zn Content and Uptake At Late Vegetative Stagesupporting
confidence: 93%
“…The treatment foliar spray of 0.5 % TNAU Zn EDTA (T 10 ) recorded significantly higher Zn content and control (NPK alone -T 1 ) recorded lowest Zn content. This is in agreement with the findings of Teixeira et al, (2019) who reported that Zn content and Zn uptake in the Mombasa grass was directly proportional to the rate of foliar applied chelated Zn, contributing to the yield of better quality forage. The improvement in the Zn concentration and uptake observed in this experiment comparing ZnSO4 and Zn-EDTA, is similar to that reported by Gangloff et al, (2002).…”
Section: Zn Content and Uptake At Late Vegetative Stagesupporting
confidence: 93%
“…Brazilian livestock needs to ally productivity and sustainability, very divergent purposes that are being demanded by the population increase, climatic changes and behavior of consumers. In this context, the discovery and use of rational technologies are essential, since the increase in the meat and milk production are only achieved with large quantities of chemical fertilizers and openings in new areas (Teixeira et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The edaphoclimatic conditions and the great territorial extension are factors that, since the beginning of the Brazilian livestock, define an important characteristic of this activity, to have almost the whole of the herd raised in pastures, which constitute in the most practical and economic way to produce and to feed the cattle (Sá et al 2019;Teixeira et al 2019).…”
Section: Introductionmentioning
confidence: 99%